What is thinking? : and other philosophical reflections - Das, Saitya Brata (Delhi, India : Aakar, 2021)
The philosophical essays of this collection argue, each time from a singular perspective, that the task of thinking is to release the element of the undconditional from various closures, and thus to make it manifest as the true and the essential task of our individual and social existence. Naming this unconditional element as the "messianic", the book displays the profound ethico-political significance of messianic thought for our contemporary world. "To think is to thank: thinking and thanking, denkena and danken, in their very proximity-as Martin Heidegger remars-bring together an event that will one day give birth to the dancing start that will shine against the dark night in which we exist today.
Includes bibliographical references (pages 142-143).
Keywords: Thought and thinking; Questioning; Death